Evolution of Conceptual Foundations of Early Childhood Education in the Federal Republic of Germany: From Care-Based to Educational-Developmental Model - Honcharuk, Maryna (Educological discourse, 2025)
The article examines the transformation of German early childhood education from a predominantly care-based model to a modern educational-developmental system over recent decades. The aim of the study is to analyze the evolution of conceptual foundations of early childhood education in the Federal Republic of Germany and substantiate the significance of this experience for modernizing Ukrainian early childhood education. The research methodology is based on a comparative-pedagogical approach using methods of theoretical analysis, synthesis, comparison of regulatory documents, scientific works of German researchers, and systematization of practical experience of early childhood institutions functioning in German federal states. Key stages of evolution from Friedrich Froebel's ideas to contemporary federal initiatives for improving early childhood education quality are analyzed. Conceptual changes in understanding the role of kindergartens from simple childcare to full-fledged educational institutions ensuring comprehensive child development are examined. Special attention is paid to regulatory changes, particularly the adoption of the «Early Childhood Development and Education Act» (2008) and the Kindergarten Quality Act» (2022), which established the new status of early childhood education in the German educational system. Research results indicate the systematic nature of transformation encompassing conceptual, organizational, and practical aspects of early childhood institutions functioning. Key characteristics of this transformation include elevating early childhood education status to a full educational level, implementing competency-based approaches, professionalizing pedagogical staff, developing inclusive education, and creating high-quality educational environments. Conclusions confirm the importance of German experience for modernizing Ukrainian early childhood education, especially in the context of European integration. Key aspects of the German model for adaptation are identified: developing clear quality standards, improving pedagogical staff qualifications, implementing modern teaching methods, and developing inclusive education.